2014
DOI: 10.1111/jpim.12176
|View full text |Cite
|
Sign up to set email alerts
|

PERSPECTIVE: Older Adults' Adoption of Technology: An Integrated Approach to Identifying Determinants and Barriers

Abstract: Technology has recently begun to be explored as a way to cope with the challenges related to the aging of the population. However, while many technological systems for older adults have entered the market, the rate of adoption is low despite the potential benefits they intend to provide. The market response suggests that older adults' adoption of technology is not simply a matter of performance and price, but a complex issue that is affected by multiple factors. To address the issue in a more comprehensive way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
405
1
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 540 publications
(480 citation statements)
references
References 68 publications
19
405
1
22
Order By: Relevance
“…Of least concern to older people when adopting ATs are feeling of embarrassment, autonomy and loss of dignity. The identified underlying factors (see table 1 Full-text articles assessed for inclusion (n = 44) [39,42,55] 3…”
Section: Discussionmentioning
confidence: 99%
“…Of least concern to older people when adopting ATs are feeling of embarrassment, autonomy and loss of dignity. The identified underlying factors (see table 1 Full-text articles assessed for inclusion (n = 44) [39,42,55] 3…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for chronic pain that is often highly variable. (34) They also indicated that a simple interface, technical support, and clear instructions are needed to tackle the technological barriers, consistent with other studies (29,35). App interface customization was also a recurring theme across the focus group discussions, to tailor the app to individual needs and preferences of the users, and to accommodate hearing and visual impairment, further underlining the need for usability and accessibility.…”
Section: Discussionmentioning
confidence: 56%
“…Several previous studies also have found that anxiety is positively correlated with age while self-efficacy is negatively correlated, resulting in lower self-confidence and higher anxiety in older adults when facing new technology (27,32). As Lee and Coughlin point out (33), it is important to build an intuitive design to enhance selfconfidence among older adults. Our focus group results point to the fact that a smartwatch provides a sufficient degree of familiarity by resembling a regular watch, thus facilitating knowledge transfer and overcoming the learning barriers, possibly building confidence in older adults' ability to use this new technology (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations